2016
DOI: 10.3390/ijms17071174
|View full text |Cite
|
Sign up to set email alerts
|

La Autoantigen Induces Ribosome Binding Protein 1 (RRBP1) Expression through Internal Ribosome Entry Site (IRES)-Mediated Translation during Cellular Stress Condition

Abstract: The function of ribosome binding protein 1 (RRBP1) is regulating the transportation and secretion of some intracellular proteins in mammalian cells. Transcription of RRBP1 is induced by various cytokines. However, few studies focused on the process of RRPB1 mRNA translation. The RRBP1 mRNA has a long 5′ untranslated region that potentially formed a stable secondary structure. In this study, we show that the 5′ UTR of RRBP1 mRNA contains an internal ribosome entry site (IRES). Moreover, the RRBP1 expression is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
(49 reference statements)
1
15
0
Order By: Relevance
“…Our data demonstrate that riluzole can display synergistic anti-GBM effects with mTOR inhibitors (see Figure 5C) and recent data have demonstrated that riluzole synergizes with the chemotherapeutic paclitaxel in triple-negative breast cancers [53]. It is well known that chemotherapeutically induced cellular stress can activate IRES-mediated protein synthesis of various transcripts, including the aryl hydrocarbon receptor, ATF2, ribosome binding protein 1, c-myc and β-catenin [54][55][56][57][58]. While c-myc IRES-dependent translation is mediated via hnRNP A1, it is tempting to speculate that these other IRES containing mRNAs may also be regulated via hnRNP A1 activity and that these compounds may be utilized to identify other transcripts subject to hnRNP A1-mediated IRES regulation.…”
Section: Discussionsupporting
confidence: 71%
“…Our data demonstrate that riluzole can display synergistic anti-GBM effects with mTOR inhibitors (see Figure 5C) and recent data have demonstrated that riluzole synergizes with the chemotherapeutic paclitaxel in triple-negative breast cancers [53]. It is well known that chemotherapeutically induced cellular stress can activate IRES-mediated protein synthesis of various transcripts, including the aryl hydrocarbon receptor, ATF2, ribosome binding protein 1, c-myc and β-catenin [54][55][56][57][58]. While c-myc IRES-dependent translation is mediated via hnRNP A1, it is tempting to speculate that these other IRES containing mRNAs may also be regulated via hnRNP A1 activity and that these compounds may be utilized to identify other transcripts subject to hnRNP A1-mediated IRES regulation.…”
Section: Discussionsupporting
confidence: 71%
“…RRBP1, an endoplasmic reticulum membrane protein, is mainly located on the endoplasmic reticulum membrane and plays an important role in the transportation and secretion of nascent proteins. 9 , 11 , 15 Moreover, RRBP1 is crucial for the terminal differentiation of secretory tissues and the procollagen biosynthesis of secretory tissues. 16 19 Recently, RRBP1 has been reported to be connected to the regulation of unfolded protein response signaling molecules and the accumulation of perinuclear autophagosomes of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Renilla luciferase (first cistron, RL) and firefly luciferase (second cistron, FL) was described previously (31,32). To obtain plasmids pR-NRF-F and pR-AHR-F, we inserted the 5'-UTRs of AHR and NRF which were synthesized by Sangon Biotech.…”
Section: Construction Of Dicistronic Reporter Plasmids the Initial Dmentioning
confidence: 99%
“…To determine if the AHR 5'-UTR contains an IRES, we employed the dicistronic reporter plasmid pRF (31). The dicistronic construct contains a Renilla luciferase (RL) open reading frame (ORF) and a firefly luciferase (FL) ORF that are separated by an intercistronic region.…”
Section: Analysis Of Ires Activity In the 5'-utr Of Ahr Mrnamentioning
confidence: 99%